THE PREVALENCE OF HUMAN IMMUNODEFIENCY VIRUS-1 (HIV-1) SUBTYPES AND TRANSMISSION METHOD AMONG HIV/AIDS INFECTION PATIENT IN TULUNGAGUNG, EAST JAVA INDONESIA - Ardianto, Achmad; Khairunisa, Siti Qamariyah; Kotaki, Tomohiro; Witaningrum, Adiana Mutamsari; Qushay, M.; Juniastuti, Juniastuti; Rahayu, Retno Pudji; Widiyanti, Prihartini; Utomo, Budi; Lusida, Maria Inge; Nasronudin, Nasronudin (Institute of Topical Disease Universitas Airlangga, 2015)
The rapid epidemic growth of HIV is continuing in Indonesia. There are some factors which have influenced the spreading of this epidemic in Indonesia, such as the poor awareness to avoid unsafe free sex attitude and the sharing of needles and syringes among intravenous drug users (IDUs). The sexual transmission of HIV has also apparently increased in Tulungagung. Commercial sex workers play a significant role in the spread of HIV in Tulungagung. People in Tulungagung have worked at other countries as Indonesian migrants. This condition can cause the increase number of HIV-1 case and the possibility of genetic variation (subtype) HIV-1 in Tulungagung. This research is aimed to analyze the subtype and to determine estimation of transmission mode on infected patient of HIV-1 and AIDS who came to Seruni clinic Dr. Iskak hospital in Tulungagung. 40 HIV?AIDSpatients were interviewed to determine the subtype and the transmission mode. The results showed that 14 of 40 plasma samples (35%) were successfully to amplified and sequenced. OverallCRF01-AE wereidentified as predominant subtype among HIV/AIDS patients in Tulungagung. Based on individual information, 31 of 40 subjects (77%) were heterosexual transmission.